Exploring and describing management action for the pursuit of disruptive innovation - Thomond, Peter Nicholas (Cranfield University, 2004)
Disruptive Innovation as a theory is often misunderstood and as a term it tacks clear definition. Moreover, there is an absence in existing research of a coherent framework to explain the qualitative factors that management practitioners face when attempting to pursue disruptive innovation as part of a balanced approach to innovation management. I In response to these problems, this thesis describes a researcher-led collaborative academic- industrial exploration of disruptive innovation. The research was conducted in three waves; first to generate an holistic appreciation of the organisational effort required in the pursuit of disruptive innovation; second to generate focus; third to explore a primary area of management action that constrains businesses to the pursuit of incrementalism. New qualitative knowledge was generated, based upon the experiences and insights of 127 industrialists from four case study organisations, 11 experts and the researcher's observations over a 33 month period. Findings suggest that the theory of disruptive innovation fails to be translated into practice because managers lack an holistic appreciation of th e innovation agenda. When this is the case, disruptive opportunities invoke management cognitions that drive disruptive innovation rejection strategies. In effect, managers allow their prevailing mental models to dictate an imbalanced focus upon steady-state, sustaining innovation. However, it was found that such inhibitors can be challenged by the use of adjusted portfolio management approaches. The research is primarily exploratory and provides the basis for a new, more grounded understanding of the pursuit of disruptive innovation in average performing organisations.